In silico identification and biological evaluation of a selective MAP4K4 inhibitor against pancreatic cancer. (31st December 2023) - Chang, Chao-Di; Chao, Min-Wu; Lee, Hsueh-Yun; Liu, Yi-Ting; Tu, Huang-Ju; Lien, Ssu-Ting; Lin, Tony Eight; Sung, Tzu-Ying; Yen, Shih-Chung; Huang, Sing-Han; Hsu, Kai-Cheng; Pan, Shiow-Lin
Abstract: Inhibiting a specific target in cancer cells and reducing unwanted side effects has become a promising strategy in pancreatic cancer treatment. MAP4K4 is associated with pancreatic cancer development and correlates with poor clinical outcomes. By phosphorylating MKK4, proteins associated with cell apoptosis and survival are translated. Therefore, inhibiting MAP4K4 activity in pancreatic tumours is a new therapeutic strategy. Herein, we performed a structure-based virtual screening to identify MAP4K4 inhibitors and discovered the compound F389-0746 with a potent inhibition (IC50 120.7 nM). The results of kinase profiling revealed that F389-0746 was highly selective to MAP4K4 and less likely to cause side effects. Results of in vitro experiments showed that F389-0746 significantly suppressed cancer cell growth and viability. Results of in vivo experiments showed that F389-0746 displayed comparable tumour growth inhibition with the group treated with gemcitabine. These findings suggest that F389-0746 has promising potential to be further developed as a novel pancreatic cancer treatment. Graphical abstract: UF0001 Highlights: We identified a novel MAP4K4 inhibitor using a structure-based virtual screening strategy. Kinase profiling showed high selectivity towards MAP4K4. The identified inhibitor suppressed pancreatic cancer cell growth and viability in vitro. The inhibitor downregulated the MKK4-JNK signalling pathway. The inhibitor suppressed tumour growth in vivo.